Feeding of Marbled Goby, Oxyeleotris marmorata (Blkr.), Larvae in the Two Weeks of Their Early Life - Effendi, Irzal; Sumawidjaja, K. (Jurnal Akuakultur Indonesia, 2002)
ABSTRACTThe experiment was carried out at the Laboratory of Aquaculture System and Technology, Faculty of Fisheries, Institut Pertanian Bogor, Bogor. Factorial arrangement in randomised block design was used in this experiment with two factors: kind of feed and feed density for sand goby, Oxyeleotris marmorata (Blkr.) larvae. There were 3 kinds of feed: rotifer, enriched-rotifer, and egg yolk-premix. Rotifer density of 20, 30, and 40 individuals/ml were maintained troughout the experiment. Egg yolk-premix were given per day in equivalent quantity as those rotifers in the treatment. Larvae of 40 individuals/l were kept in the 250 l plastic tanks, filled with 200 l of aerated ground water for 15 days indoor. Larvae fed rotifer showed better survival and growth rate than those fed egg yolk-premix. Increased rotifer density tended to increase survival and growth rate of larvae.Key words :  marbled goby, Oxyeleotris marmorata, larvae, feeding, rotifers ABSTRAKPercobaan ini dilakukan di Kolam Percobaan Babakan, Laboratorium Bogor, Bogor, dan dirancang berbentuk factorial dalam rancangan acak kelompok, dengan faktor: (1) jenis pakan dan (2) kepadatan pakan. Jenis pakan dibedakan menjadi: rotifera, rotifera-diperkaya, dan kuning telur-premiks, sedangkan kepadatan rotifera dibedakan menjadi : 20,30, dan 40 individu/ml, dipertahankan setiap hari. Kuning telur-premiks diberikan kepada larva ikan betutu, Oxyeleotris marmorata setiap hari yang setara dengan bobot rotifera setiap perlakuan, berdasarkan bobot kering keduanya. Larva sebanyak 40 ekor/l dipelihara dalam tangki plastik bervolume 250 l yang diisi air 200 l selama 15 hari dalam ruangan. Larva yang diberi rotifera cenderung memiliki kelangsungan hidup dan pertumbuhan lebih besar daripada kuning telur-premiks. Kepadatan rotifera yang semakin tinggi cenderung dapat meningkatkan kelangsungan hidup dan pertumbuhan larva.Kata kunci :  ikan betutu, Oxyeleotris marmorata, larva, pemberian pakan, rotifera